Rola rodziny w interwencji i profi laktyce zagrożeń w Internecie - Knol-Michałowska, Kamila (Wydawnictwo Naukowe UAM, 2012)
Nowadays the Internet is an integral part of young people’s lives. However, instead of many possibilities and positive aspects arising from Internet use, adults identify a selection of online risks connected to children online activities. Describing the risks, families express apprehension about adolescents’ safety and indicate fi elds of concerns which need to be covered in parental intervention and prevention strategies. Often this might be a challenge for families due to their inadequate knowledge or skills. Researches show that even though increasing numbers of adults use the Internet, they perceive their skills as less advanced than adolescents’. Under these circumstances, the main subjects of analysis in this article were as follows: differences in Internet usage among adults and adolescents, current intervention and prevention strategies developed by families, areas of parental education provided by organizations involved in disseminating information about online safety.
The Role of Families in Online Risks Prevention and Intervention
Keywords: online risks; Internet; family; prevention strategies; intervention strategies